Interactions Between the Neuroendocrine System and T Lymphocytes in Diabetes - Andreone, Luz; Gimeno, María Laura; Perone, Marcelo J. (Frontiers in Endocrinology, 2018)
It is well established the fine-tuned bidirectional communication between the immune and neuroendocrine tissues maintaining homeostasis. Several types of immune cells, hormones and neurotransmitters of different chemical nature are involved as communicators between organs. Apart of being key players of the adaptive arm of the immune system, it has been recently described that T lymphocytes are involved in the modulation of metabolism of several tissues in health and disease. Diabetes may result mainly from lack of insulin production (type 1 diabetes) or insufficient insulin and insulin resistance (type 2 diabetes) both influenced by genetic and environmental components. Herein, we discuss accumulating data regarding the role of the adaptive arm of the immune system in the pathogenesis of diabetes; including the action of several hormones and neurotransmitters influencing on central and peripheral T lymphocytes development and maturation, particularly under the metabolic burden triggered by diabetes. In addition, we comment on the role of T effector lymphocytes in adipose and liver tissues during diabetes, which together enhances pancreatic beta-cell stress aggravating the disease.